2018
DOI: 10.1590/s1679-45082018ao4351
|View full text |Cite
|
Sign up to set email alerts
|

Trends in surgical treatment of femoral neck fractures in the elderly

Abstract: Objective To analyze recent demographic and medical billing trends in treatment of femoral neck fracture of American elderly patients.Methods The American College of Surgeons National Surgical Quality Improvement Program database was analyzed from 2006 to 2015, for patients aged 65 years and older, using the Current Procedural Terminology codes 27130, 27125, 27235, and 27236. Patient demographics, postoperative complications, and frequency of codes were compared and analyzed over time. Our sample had 17,122 el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
1
12
0
6
Order By: Relevance
“…Several studies have looked at trends in surgical treatment strategies for patients experiencing native femoral neck fractures . Most have found that HA is the most common treatment modality, with rates ranging from 60% to 75% of all surgically treated fractures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have looked at trends in surgical treatment strategies for patients experiencing native femoral neck fractures . Most have found that HA is the most common treatment modality, with rates ranging from 60% to 75% of all surgically treated fractures.…”
Section: Discussionmentioning
confidence: 99%
“…All inpatient and post‐discharge events are recorded through the 30th postoperative day. This database has been used successfully in reporting trends in orthopedic surgery, including in assessing native femoral neck fractures …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Femoral neck fractures (FNF) are common in the geriatric population and they represent a significant health care problem and have an enormous impact on health insurance costs [1,2]. The fragile physical health of this age group often leads to risks of post-operative morbidity, complications and even mortality.…”
Section: Introductionmentioning
confidence: 99%